PENGARUH PENDEKATAN MASTERY LEARNING DENGAN POLA KELOMPOK REMEDIAL TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Arusman Arusman (Lantanida Journal, 2019)
The results of recapitulation of UN scores students on static fluid material from 2014-2016 have fluctuated every year. Many factors affect these conditions, one of which is the use of learning methods that are more memorized and low motivation to learn students. Mastery learning approach to learning with remedial group patterns allows can change the mindset of students and can improve learning outcomes. This study aims to determine the effect of the mastery learning approach with remedial group patterns on student learning outcomes. The method used in this research is quasi experiment research, which involves 4 (four) classes with remedial patterns per class. Data collection is done by using multiple-choice test questions. The test result data were analyzed using the one way ANOVA test formula. The results of the statistical test show that Fcount> Ftable is 2.90> 2.72 for a significant level of 95% and α = 0.05. The results showed that Ha hypothesis was accepted. The conclusion that there is an effect of the mastery learning approach with the remedial group pattern on learning outcomes, this can be seen from an increase in the class with the incomplete remedial pattern of selective friends (TTT-PT), compared with other classes.